The Systematic Review: The impact of minimally invasive techniques on the outcomes of inguinal hernia repair - Grys, Maria; Piotraszewska, Marta; Bartold, Magdalena; Kochański, Filip; Pohrybieniuk, Janina; Wołk, Karolina; Błonka, Dominika; Pietrzak, Jan; Jaskulska, Aleksandra; Skudzińska, Magda (Quality in Sport, 2025)
Background This review examines the impact of minimally invasive techniques—laparoscopic (TEP, TAPP) and robotic—on inguinal hernia repair outcomes. Based on literature from 2020–2025, it shows that when performed by experienced surgeons, these methods offer faster recovery, less pain, and recurrence rates comparable to open surgery. Robotic repair is particularly promising for complex cases, though it involves higher costs and longer operative times. The review emphasizes the importance of tailoring surgical choices to the surgeon’s expertise, patient profile, and healthcare resources. Aim of the Study The study aims to evaluate the impact of minimally invasive techniques on the outcomes of inguinal hernia repair. Materials and methods This systematic review focuses on laparoscopic and robotic repairs compared to open surgery. Outcomes analyzed include operative time, postoperative pain, hospital stay, recurrence, complications, and patient quality of life. Studies published between 2018 and 2025 were sourced from PubMed, MEDLINE, Scopus, Embase, and the Cochrane Library. Included studies span randomized trials, cohort studies, meta-analyses, and systematic reviews. Methodological quality was critically assessed. Results Minimally invasive techniques—especially robotic and laparoscopic repairs—were associated with faster recovery, lower postoperative pain, and shorter hospital stays than open repair. Although robotic surgery had longer operative times, this improved with experience. Recurrence rates were similar across techniques, while robotic repairs showed fewer complications. Conclusions Minimally invasive approaches improve patient outcomes in inguinal hernia repair. Laparoscopic and robotic methods reduce pain and hospital stay. Robotic surgery is beneficial for complex cases but requires more resources and training. Surgical approach should be tailored to the patient and institutional capability.